In situ ambient pressure XPS study of Pt/Cu(111) single-atom alloy in catalytically relevant reaction conditions. (24th February 2021) - Simonovis, Juan Pablo; Hunt, Adrian; Waluyo, Iradwikanari
Abstract: The presence of multiple reactant gases as well as reaction intermediates in a heterogeneous catalytic reaction results in a complex interaction between different components of the catalyst with each gas, which can alter the surface and chemical state of the catalyst differently than in the presence of an individual gas alone. In this study, we used in situ ambient pressure x-ray photoelectron spectroscopy to study the surface state of Pt/Cu(111) single-atom alloy model system in two catalytically relevant reaction conditions: CO2 hydrogenation and CO oxidation. We found that the activation of CO2 results in the formation of CO, which adsorbs on Pt sites at up to 400 K. In the presence of CO2 and H2, Pt catalyzes the reverse water–gas shift reaction, which produces more CO and further stabilizes surface Pt atoms at 450 K. On the other hand, in CO oxidation condition, the presence of O2 results in the formation of a thick Cu2 O layer at higher temperatures, and Pt atoms are no longer detected in the surface and subsurface layers. When O2 is introduced to the sample before CO, the formation of a complete Cu2 O layer that covers all Pt atoms occurs immediately at room temperature. However, when CO is introduced at room temperature before O2, the presence of adsorbed CO on Pt sites stabilizes the surface Pt atoms and prevents the formation of a complete Cu2 O layer, thus exposing the Pt atoms in 'holes' in the Cu2 O layer.